The interplay of sun damage and genetic risk in Australian multiple and single primary melanoma cases and controls. (5th February 2020) - McMeniman, E.K.; Duffy, D.L.; Jagirdar, K.; Lee, K.J.; Peach, E.; McInerney‐Leo, A.M.; De'Ambrosis, B.; Rayner, J.E.; Smithers, B.M.; Soyer, H.P.; Sturm, R.A.
Summary: Background: Skin phenotype, host genotype and ultraviolet (UV) damage play a role in the development of melanoma. Objectives: To ascertain whether the level of UV damage at the site of melanomas was associated with genetic polymorphisms. Methods: Deep phenotyping was performed on 1244 individuals; 281 with multiple primary melanomas (MPMs), 304 with single primary melanoma (SPM) and 659 convenience controls. Genotype data was generated using the Illumina CoreExome microarray platform, assaying over 500 000 single‐nucleotide polymorphisms. A subset of variants were combined to assess a polygenic risk score (PRS) for melanoma. Results: Most MPM cases were diagnosed in patients aged > 40 years, in sites with visible chronic UV damage. Women and those diagnosed at age ≤ 40 years were less likely to have perilesional UV damage. Patients with MPM had higher frequencies of MITF E318K, MC1R R‐alleles and the ASIP risk haplotype. Individuals who had melanoma in a visibly UV‐damaged site were more likely to carry MC1R rs75570604 [odds ratio (OR) 2·5], 9q31.2 rs10816595 (OR 1·4) and MTAP rs869329 (OR 1·4). These same alleles were more common in patients with MPM who were diagnosed at age ≤ 40 years. The mean PRS was significantly higher in MPM than in SPM and controls. Naevus count was comparable in early‐onset MPM cases and those diagnosed at age > 40 years. Conclusions: Our cohort demonstrated higher frequencies of previously reported alleles associated with melanoma. MPM melanomas more commonly occur in UV‐damaged areas, and these individuals are more likely to carry MC1R red hair colour alleles. Awareness of the interplay of genetic vulnerability with UV damage can stratify risk and guide recommendations for melanoma screening. What's already known about this topic? Skin phenotype, host genotype and ultraviolet (UV) damage all play a role in melanoma development. One of the main risk factors is a personal history of melanoma; second and subsequent primary melanomas account for over 20% of all melanomas registered in Queensland. Multiple loci are associated with melanoma risk, including many low‐penetrance loci, which may have a cumulatively significant risk. Population‐wide screening programmes for melanoma are not yet economically viable. What does this study add? Patients diagnosed with melanoma at age ≤ 40 years were more likely than older patients to have melanomas in non‐UV‐damaged sites. Patients with multiple melanomas had higher frequencies of MITF E318K, MC1R R‐alleles, and the ASIP extended risk haplotype than patients with single melanoma. CDKN2A, MC1R and MTAP variants were more frequent in patients who developed melanomas at a younger age, but also in those whose melanomas were all on visibly UV‐damaged sites. What is the translational message? Incorporating these genetic findings into the known risk factors of skin phenotype and visible UV damage may allow for a more customized and economically feasible approach to early detection of melanoma, particularly in younger patients. Plain language summary available online